Construction and Interpretation of Particle Size Distribution Spectra From 19 Ecopath Models of Chinese Coastal Ecosystems - Zhai, Lu; Pauly, Daniel (Frontiers in Marine Science, 2020)
To assess the changes that fisheries have imposed on the functioning of coastal marine ecosystems in China, nineteen published Ecopath models were used to construct particle size distribution (PSD) spectra. The results show that high biomass of jellyfish from ranching operation impacted almost all of the ecosystems studied here. As well, an increasing impact of fisheries was demonstrated, via steeper PSD slopes, for ecosystems with models covering two or more periods. Models of nearshore areas, i.e., bays and estuaries, exhibited steeper PSD slopes that models of offshore areas. The PSD slopes were also correlated with total catch (TC), with the mean trophic level of catch and with the Shannon-Wiener diversity index (H’) that can be computed from Ecopath models. A multiple regression predicting the PSD slopes from year and mean trophic level of the catch explained 38.5 % of the variance in the slopes. Overall, this study confirmed the status of depletion in China’s marine fisheries resources. Also, it established that including a PSD while constructing an Ecopath model, which is straightforward, will improve it, and allow more insights to be obtained from it regarding the impact of fishing on marine ecosystems.